2016
DOI: 10.1017/s0031182016002237
|View full text |Cite
|
Sign up to set email alerts
|

Oligopeptidase B and B2: comparative modelling and virtual screening as searching tools for new antileishmanial compounds

Abstract: Leishmaniasis are diseases caused by parasites of the genus Leishmania and transmitted to humans by the bite of infected insects of the subfamily Phlebotominae. Current drug therapy shows high toxicity and severe adverse effects. Recently, two oligopeptidases (OPBs) were identified in Leishmania amazonensis, namely oligopeptidase B (OPB) and oligopeptidase B2 (OPB2). These OPBs could be ideal targets, since both enzymes are expressed in all parasite lifecycle and were not identified in human. This work aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…These findings were expected, since OPB sequence conservation was observed among Leishmania species. The lack of OPB in mammals has prompted some groups to search for potential OPB or OPB/OPB2 inhibitors as eventual drugs for leishmaniasis (Goyal et al ., 2014; Sodero et al ., 2017). The conservation in OPB activity among the 3 species analysed ( L. ( L. ) major and L. ( L. ) donovani and L. ( L. ) amazonensis , in this work) suggests that drugs designed for 1 species would probably be effective for others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were expected, since OPB sequence conservation was observed among Leishmania species. The lack of OPB in mammals has prompted some groups to search for potential OPB or OPB/OPB2 inhibitors as eventual drugs for leishmaniasis (Goyal et al ., 2014; Sodero et al ., 2017). The conservation in OPB activity among the 3 species analysed ( L. ( L. ) major and L. ( L. ) donovani and L. ( L. ) amazonensis , in this work) suggests that drugs designed for 1 species would probably be effective for others.…”
Section: Discussionmentioning
confidence: 99%
“…OPB-2 amino acid sequences are conserved among Leishmania but display several insertions and deletions and a C-terminal extension domain when compared to OPBs (de Matos Guedes et al, 2008). No enzymatic or functional studies for OBP-2 were reported to date, but comparative modelling indicates that L. (L.) amazonensis OPB and OPB2 have many similarities and may be sensitive to dual inhibitors (Sodero et al, 2017). OPB is secreted by Leishmania, as it was found in exosomes shed by L. (L.) donovani and L. (L.) major promastigotes (Silverman et al, 2008(Silverman et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%